(untitled) (SYNAPSES: INSIGHTS ACROSS THE DISCIPLINES, 2025)
The education system of the United States is a complex and diverse structure that encompasses multiple levels and institutional types, reflecting the country’s federal approach to governance and emphasis on educational accessibility. This article examines the major components of the U.S. education system, including preschool (early childhood education), secondary education (middle and high schools), and higher education (colleges and universities).